Exploring the link between childhood stress and oral diseases - Mohammad AlDomyati, Roaa; Alghazzawi, Faraned Nidhal; Yaghmour, Omnia Talal; Almarri, Haifa Ahmed; Aldaghriry, Waad Khalid; Alkahtani, Hifa Mohammed; Abdulbari, Yara Ibrahim (International Journal Of Community Medicine And Public Health, 2025)
Childhood stress, particularly as a consequence of adverse childhood events such as physical, emotional, or psychological abuse, has emerged as a significant determinant of long-term health outcomes, including oral health. This narrative review examines the intricate interplay between early-life stress and the development of oral diseases in children, elucidating the psychobiological mechanisms that underpin these associations. Stress activates the hypothalamic-pituitary-adrenal axis, resulting in elevated cortisol levels, which, over time, can dysregulate immune responses and promote chronic inflammation. These physiological alterations critically compromise the oral cavity’s defensive mechanisms, thereby increasing susceptibility to conditions such as dental caries, periodontitis, and oral soft tissue lesions. Empirical studies have established a robust correlation between elevated salivary cortisol levels and the presence of chronic periodontal disease, suggesting that psychological stress plays a crucial role in the progression of oral inflammation and tissue destruction. Furthermore, stress-induced behaviors, including bruxism, poor dietary habits, and inadequate oral hygiene practices, exacerbate the risk of oral diseases. Bruxism, in particular, has been extensively documented in children exhibiting psychological distress and is associated with temporomandibular joint disorders and dental attrition. Children exposed to adverse childhood events are also more prone to developing early childhood caries; if left untreated, early childhood caries can lead to long-term oral complications, including malocclusion, altered facial growth, and compromised masticatory function. This review also addresses the socioeconomic and environmental factors that contribute to the burden of stress and oral disease, highlighting the impact of parental stress and family adversities. The evidence underscores a robust, multifactorial relationship between early-life stress and adverse oral health outcomes. A comprehensive understanding of these associations is essential for the development of integrated preventive strategies that encompass both psychological and dental care. The early identification of at-risk children, coupled with the implementation of multidisciplinary interventions, may effectively mitigate the long-term implications of childhood stress on oral health and overall well-being.